2008
DOI: 10.3168/jds.2007-0602
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Affecting Calving Traits in Danish Holstein Cattle

Abstract: The objectives of this study were 1) to detect quantitative trait loci (QTL) affecting direct and maternal calving traits at first calving in the Danish Holstein population, 2) to distinguish between pleiotropic and linked QTL for chromosome regions affecting more than one trait, and 3) to detect QTL affecting stillbirth and calving difficulties but not calf size that could be used in selection to improve calving performance. Progeny-tested sons (2,297) were genotyped for 356 microsatellites in 34 grandsire fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
41
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 19 publications
14
41
2
Order By: Relevance
“…The first one, transmembrane protein 130 ( TMEM130 ) on BTA25 was also detected by Wu et al [38], that was associated with animal size and capacity in Chinese Holstein. Meanwhile, this gene is within a QTL region affecting calf size reported in Danish Holstein cattle[39]. In 2014, Zhao et al [40] has identified a selective signature in seven dairy and beef cattle breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The first one, transmembrane protein 130 ( TMEM130 ) on BTA25 was also detected by Wu et al [38], that was associated with animal size and capacity in Chinese Holstein. Meanwhile, this gene is within a QTL region affecting calf size reported in Danish Holstein cattle[39]. In 2014, Zhao et al [40] has identified a selective signature in seven dairy and beef cattle breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be the family structure of the REF and VAL datasets. The REF population was from an earlier within-family linkage study for QTL mapping [14]. Therefore, in the REF we expect to have larger half sib families.…”
Section: Discussionmentioning
confidence: 99%
“…This SNP is located within an intron of the TRPC1 gene, which was shown to regulate osteoblast formation in mice [114]. Cole et al [30] reported a common SNP (ss86324977) on chromosome 18 in an intronic region of the sialic acid-binding Ig-like lectin-5 (SIGLEC5) gene, associated with sire and daughter calving ease, that was also reported to affect direct calving traits in multiple studies [30,80,133,149]. In humans this gene is expressed in the placenta and has been suggested to have a role in the initiation of parturition [21].…”
Section: Genomic Regions and Genes Affecting Multiple Traits In Dairymentioning
confidence: 99%